Determinants of Customer Satisfaction in the Coffee Chain Industry: Evidence from Malaysia - Lay Hong Tan; Abrisam Abassy Shaiful Nasri; Aderline Shi Han Ong; Adlyn Syamsina Abdul Halim; Ahmad Reza Palavi Hamat; Namit Das; Neha Treesa D; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
As a globally recognized coffeehouse chain, Starbucks operates in a highly competitive industry where understanding customer preferences is essential for sustaining a competitive advantage. This study examines the determinants of customer satisfaction among coffee chain customers in Malaysia, using Starbucks as the focal case context, with emphasis on product quality, price fairness, service quality, and brand image. A quantitative research design was employed, and data were collected from 200 Starbucks customers through an online questionnaire. The data were analyzed using SPSS, including reliability analysis, Pearson correlation, and multiple regression analysis. The results indicate that the model explains 62.7% of the variance in customer satisfaction (R² = 0.627, F = 81.968, p 0.001). All four variables were found to be statistically significant predictors, with price fairness emerging as the strongest determinant (? = 0.299, p 0.001), followed by brand image (? = 0.240, p 0.001), service quality (? = 0.203, p 0.01), and product quality (? = 0.167, p 0.05). The findings suggest that customer satisfaction is driven more by perceived value and brand-related factors than by product attributes alone. Practically, managers should emphasize value-based strategies while maintaining consistent service quality to enhance customer satisfaction.